Context: The Foundation of Close Reading of Primary Source Texts. Issue 2 (1st July 2014) - Neumann, Dave; Gilbertson, Nicole; Hutton, Lisa
Abstract : The Common Core State Standards (CCSS) invite students to engage in close reading of primary source texts from American history, but an overly rigid definition of close reading that excludes providing background knowledge threatens to undermine these efforts. This approach flies in the face of decades of research on successful reading comprehension strategies. It also rejects the extensive literature on discipline-based learning in history, which has routinely affirmed the importance of context for understanding primary source texts. Primary sources are typically drawn from a world different from that of the students in time or place, or both. Teachers should provide historical context to their students by giving them information about the time, location, and purpose for the creation of the source. They should also situate the source in a specific location—whether local, national, or international—and examine the source in relation to other events of the time. Context is not the enemy of close reading of primary sources; context is the very thing that makes close reading possible and meaningful.